Factors associated with HIV-positive status among men who have sex with men in Guinea in 2022 - Dioum, Mamadou Samba; Hessou, Septime; Millimouno, Tamba Mina; Grovogui, Fassou Mathias; Kolié, Delphin; Diallo, Thierno Saidou; Dioukhane, Elhadji Mamadou; Diallo, Elhadj Marouf; Camara, Alioune; Tounkara, Thierno Mamadou; Delamou, Alexandre; Sako, Fodé Bangaly (Frontiers in Public Health, 2025)
Introduction/Context Men who have sex with men (MSM) continue to carry a disproportionate burden of HIV in West and Central Africa, where stigma, criminalization, and legal restrictions hinder access to essential prevention and treatment services. In Guinea, data on HIV-related risk factors among MSM remain scarce. Objective This study aimed to estimate the prevalence of HIV and identify factors associated with HIV seropositivity among MSM in Guinea using nationally representative data. Methods We conducted a cross-sectional analysis of the 2022 Integrated Bio-Behavioral Surveillance (IBBS) survey data, involving 1,692 MSM aged 15 years and older from eight administrative regions. Participants were recruited through respondent-driven sampling, completed standardized behavioral questionnaires, and underwent HIV testing. Univariate and multivariate logistic regression analyses were performed to identify factors associated with HIV seropositivity. Results The overall HIV prevalence among MSM was 9.4%, with higher rates in Conakry (13.4%) and N’Zérékoré (10.5%). After adjusting for confounders, three factors were significantly associated with higher odds of HIV seropositivity: being aged 25 years or older (adjusted odds ratio [aOR] = 1.78; 95% CI: 1.25–2.54), reporting STI symptoms in the past 6 months (aOR = 2.49; 95% CI: 1.61–3.84), and lacking knowledge of a regular partner’s HIV status (aOR = 1.60; 95% CI: 1.11–2.31). Conclusion These findings highlight the need for targeted, stigma-free HIV interventions for MSM in Guinea. Strategies should emphasize STI screening, support partner disclosure, and address structural barriers to care.